Predictors of Prenatal Breastfeeding Self-Efficacy in Malaysian Women: a Cross-Sectional Study - Hamid, Syahrul Bariah Abdul; Zaidi, Nurshazlyana Mohamad (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2020)
Mothers with better self-efficacy are tend to have intent to breastfeed, initiate early and have lengthier of exclusive breastfeeding. This study aimed to evaluate the level of breastfeeding self-efficacy and to investigate the determinants of breastfeeding self-efficacy among pregnant mothers. A total of 180 expecting mothers were recruited in this cross sectional study from chosen Maternal and Child Health Clinics in Selangor. Self-administered questionnaires of Iowa Infant Feeding Attitude Score (IIFAS) and Breastfeeding Self-Efficacy (BSES-SF) were used to attain information on maternal attitudes and knowledge of breastfeeding and breastfeeding self-efficacy. Findings showed subjects had high level of breastfeeding self-efficacy (mean 51.79±11.94) and majority of them had fair knowledge in breastfeeding. Breastfeeding self-efficacy is found associated with number of children, while, residential area, occupation and household income were associated with breastfeeding knowledge (p<0.05). The best-fit regression analysis revealed three variables that explained 41.0% of the variance in breast feeding self-efficacy among expectant mothers. They were being housewife, multiparous and had positive breastfeeding attitudes (p<0.05). For that reason, healthcare providers can tactically identify women vulnerable to low breastfeeding self-efficacy by providing early intervention through increasing the awareness and knowledge in breastfeeding during prenatal and antenatal.